Creating Awareness among Young Generation in China on Modern Hanfu Design by Using Interactive Design Applications - Mengshu, Ding (UNIMAS, 2024)
The Han people are the largest ethnic group in China, and their traditional costume, Hanfu, has a rich history that reflects the formation and development of the Han nation. Modern Hanfu is a type of Hanfu that features innovative designs suitable for contemporary wear while still maintaining the typical characteristics of traditional Hanfu. In recent years, there has been a surge of interest in modern Hanfu design. However, this trend has also brought about some issues. Some designers misuse Hanfu elements, resulting in the misrepresentation of Hanfu culture. Some others just design similar-looking modern Hanfu. This highlights the importance of promoting a greater understanding of Hanfu culture and encouraging more original, high-quality designs. This study aims to raise awareness of modern Hanfu design through interactive design applications among the young generation in China. The study used a mixed research method, including semi-structured interviews with 16 respondents and a questionnaire survey with 315 respondents. The data from these sources revealed the Chinese perception of modern Hanfu design and identified areas for improvement. The respondents agree that Hanfu is essential but needs a better understanding of its cultural significance. Secondly, it discussed the suitability of using interactive design applications to educate and promote modern Hanfu. The relevant factors include lifestyle preferences, interactive design, educational information, perceived functional value, perceived emotional value, perceived risk, and communication. Lastly, the relationships between these factors were found to establish the theoretical model and guide the development of interactive design applications for modern Hanfu. The study developed a revised theoretical model and designed a digital interactive application integrating modern Hanfu interaction design and cultural dissemination. The study aims to make feasible recommendations for the sustainable development of modern Hanfu design and to raise public awareness of Hanfu culture. Keywords: Modern Hanfu design, interactive design application, young generation in China, user behaviour, Hanfu culture